Edukasi Pencegahan Asma Pada Masyarakat Di Desa Kebonsari Kecamatan Karangdadap Kabupaten Pekalongan - Dian Kartikasari; Jumaroh; Hana Nafiah (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2022)
Asthma is a disease that causes shortness of breath and cough due to inflammation of the airways. Asthma attacks caused by the patient can not perform daily activities so that it can cause decreased productivity and reduce the quality of life. Community service activities were carried out to 20 people by giving a pretest (initial observation) before being given education and a posttest (final observation) after education. The results of this community service activity showed that one day after conducting health counseling about asthma prevention, most of the 20 respondents had knowledge with a good category, namely opening 17 respondents (85%) while those with less than 3 respondents (15%). Education about asthma prevention can help the community, especially asthma sufferers, to anticipate recurrence.